Pengaruh Imbangan Tepung Ubi Jalar Ungu (Ipomea batatas L) dan Sari Kedelai (Glycine max L) terhadap Karakteristik Es Krim - Nanda Audina Sopianti; Hendrawan; Amila Khairina (Ma'soem University, 2023)
Ice cream is a frozen dessert with a lot of milk that everyone likes. One factor determining the quality of ice cream is the density of ice cream consisting of fat, protein, carbohydrate, vitamins and minerals. The sweet purple starch and soybean extract can be added into the dough to improve the density and characteristics of the ice cream as a whole. This research has been carried out to determine the balance of sweet purple starch and soybean extract the most appropriate to produce ice cream with the best characteristics. The method used in this research is the experimental method with the Acute Group Project consisting of five treatments of the balance of purple-striped wax and silk sari which are A (35:65:0), B (30:65:5), C (25:65:10), D (20:65:15), dan E (15:65:20). Each treatment was repeated five times. The results showed that treatment B, namely the addition of 5 grams of the sweet purple starch to the dough, produced the best characteristics of ice cream based on organoleptic tests of color, taste, texture and aroma.